Wait, rest, pause ebook Dormancy in nature. - Atkins, Marcie Flinchum (2019)
If you were dormant / waiting out the cold, the dry, the heat / you would pause. Captivating photos of animals accompany simple, engaging text to explain dormancy in nature. This highly curricular book teaches young readers about different kinds of dormancy and which animals do what. Featuring creatures like ladybugs, chickadees, squirrels, and even alligators, this book won't put curious kids to sleep! "A refreshingly original exploration of a physical process both common and important in the natural world."—starred, Kirkus Reviews